Culture, État et responsabilités : entretien avec Ana Sokolovic - Gendreau, Philippe (Liberté, 2007)
Publisher: Collectif Liberté

Itinéraire de quatre pionnières de la vie culturelle à Québec après 1945 - Harvey, Fernand (Les cahiers des dix, 2007)
À Québec comme partout ailleurs, la place des femmes dans la sphère publique est relativement récente. L’idée qu’une femme puisse poursuivre des études universitaires, travailler à l’extérieur de la maison ou entreprendre une carrière après le mariage a commencé à se généraliser peu avant les années 1960. Dans ce long cheminement, certaines femmes ont joué un rôle pionnier. Cet article examine le parcours de vie de quatre de ces femmes qui ont réussi à faire leur marque dans le milieu culturel et médiatique de la ville de Québec au cours des années qui ont suivi la seconde guerre mondiale : Francoise Larochelle-Roy, Simone Bussières, Georgette Lacroix et Monique Duval. L’itinéraire biographique de ces pionnières permet de mieux comprendre les singularités de leur insertion dans le milieu culturel et professionnel, en même temps que les points communs qui les relient toutes quatre au contexte d’une époque. On les suivra donc depuis l’enfance jusqu’à la vie adulte où elles évolueront dans l’enseignement, le journalisme, l’animation radiophonique, ainsi que dans le monde des lettres.
Number: 61

La rencontre des musiques du Moyen-Orient et de l'Occident : esthétisme, composition et analyse - Makdissi-Warren, Katia (Université de Montréal, 2007)
The object of this dissertation is the meeting of Middle-Eastern and Western music. The dissertation includes an essay and seven original compositions (scores and recordings). The text begins with the exposition of the basics of Middle-Eastern music required to understand my artistic approach. The 'taqasim', a major musical form in the Middle-East and a source of inspiration for my work is presented in more detail. The second chapter deals with the philosophy of aesthetics involved in the intermixing of musical cultures. Concerns about the coherence of commingled languages are exposed. The concepts of intermixing, cultural identity and coherence of a work are submitted for discussion. For a given work, does the notion of coherence retain its essence from one person to the next according to culture and social context? This questioning is directly linked to the creation and generation of the processes of development for the musical material in my compositions. Throughout the chapter, I position my approach in relation to the thinking of authors such as Adorno, but also relative to personal experiences. In chapter 3 I describe the writing processes I have developped in order to create a sound fabric wherein Middle-Eastern music meets that of the West. My work defines processes for treating parameters in order to draw together elements of both Eastern and Western musical expressions into a distinctive language <f> <fr><nu>.</nu><de>7</de></fr></f> the key to this is grasping how one musical element influences another. Using analysis as a starting point for the comparison of musical parameters in each of the languages, I have elaborated new commingling (intermixing) techniques. This chapter is therefore devoted to the cross-relational writing techniques that have been evolved to adequately support my artistic approach. The final chapters of this dissertation feature the detailed analyses of three of my compositions: 'Jet Stream, Algorythme and PLB'. Each piece's form, sections and sub-sections are presented followed by the analysis of its basic musical material and development.

A Queer Protocol of Homage: Chambres de Ténèbres/Tombeau de Claude Vivier By Marko Nikodijević - Novak, Jelena (International Journal of Music New Sound, 2007)
The music of Canadian composer Claude Vivier (1948-1983) was used as a fractalized material for the creation of the composition Chambres de ténèbres/tombeau de Claude Vivier (2005) by Marko Nikodijević. Vivier’s opus and his marginal queer acting were the pillars of Nikodijević’s meticulous reading/deconstructing of Vivier’s world through his own artistic dilemmas.

Jeanne Maubourg (1875-1953) : l’apprentissage de la modernité théâtrale - Robert, Lucie (Jeu. Revue de théâtre, 2007)
Un article de la revue Jeu, diffusée par la plateforme Érudit.